Revised Draft of the Second Five Year Plan Ajmer State 1956-61 - Planning Commission (Planning Commission, 1956)
The State of Ajmer has an area of 2417 Sq.Miles and a population of 6,93,372 Annexure I sets out some other selected basis statistics in regard to the State. Owing to its position on the water-shed of the Indian continent, which is about the utmost limit to which both the North Eastern and the South Western monsoons can roach, rainfall in this State has always been scare and ill-distributed. There are no perennial rivers and the existence of vary old rock with a shallow covering of earth precludes the possibility of the natural storing up of sub-soil water. The little rain that falls normally runs off the hard rocky surface unless it is stored in artificial reservoirs or tanks.
Government of Ajmer Development Department
Government of Ajmer Development Department